2021
DOI: 10.1101/2021.07.16.452724
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel Hendra virus variant detected by sentinel surveillance of Australian horses

Abstract: A novel Hendra virus (HeV) variant was identified from a horse that suffered acute fatal disease consistent with HeV infection through multidisciplinary and interagency syndromic sentinel surveillance research. Novel molecular assays for HeV detection are described in the light of routine testing failure. In silico analysis of the variant receptor-binding protein in comparison with prototypic HeV supported that the monoclonal antibody m102.4 used for post-exposure prophylaxis, as well as the equine vaccine, sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The detection of cross-reactive HNV antibodies (Abs) in humans and Pteropus bats in Africa underscored that 2 billion people worldwide live in regions threatened by HNV spillovers ( 6 ). Moreover, the recent discovery of a previously unknown HeV genotype ( 7 , 8 ) is an urgent reminder of the HNV zoonotic threat. To date, no approved vaccines or therapeutics for use in people exist against HNV infections ( 9 ).…”
mentioning
confidence: 99%
“…The detection of cross-reactive HNV antibodies (Abs) in humans and Pteropus bats in Africa underscored that 2 billion people worldwide live in regions threatened by HNV spillovers ( 6 ). Moreover, the recent discovery of a previously unknown HeV genotype ( 7 , 8 ) is an urgent reminder of the HNV zoonotic threat. To date, no approved vaccines or therapeutics for use in people exist against HNV infections ( 9 ).…”
mentioning
confidence: 99%
“…Finally, NiV sequences are ultimately reliant on the PCR primers used to detect the virus in the original sample. If the PCR primers are overly specific, they may systematically miss some viruses (33). Future efforts may want to consider using broader primer sets.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on herpesviruses have notably revealed that cell-cell fusion phenotype can significantly differ across isolates of the same viral species [166]. As sequences of henipaviruses detected in domestic and wild species are becoming available [167][168][169], it is important to consider a diversity of henipavirus isolates in comparative studies to understand how cell-cell fusion phenotype varies across viruses and how it correlates with spillover risk.…”
Section: Knowns and Unknowns Of Syncytium Formation And Future Directionsmentioning
confidence: 99%